Anomalous right coronary artery arising from left anterior descending artery - M.L. Sreenivas Kumar; D. Rajasekhar; V. Vanajakshamma; C.Shashanka (Journal of Clinical and Scientific Research, 2012)
A 54-year-old male patient presented with acute myocardial infarction involving left anterior descending and right coronary artery territories. Coronary angiogram showed a single coronary artery with right coronary artery arising from left anterior descending artery (LAD), which coursed anterior to right ventricular outflow tract and thrombotic lesion in mid left anterior descending artery before origin of right coronary artery. The patient was treated with thrombolytic therapy and glycoprotein IIb/IIIa inhibitors. Anomalous origin of right coronary artery as a branch of LAD is a very rare type of congenital coronary artery anomalies. It is important to recognize this anomaly as it can be associated with extensive myocardial ischemia and sudden cardiac death in young persons even without atherosclerosis.